Pengaruh Lingkungan Kerja, Motivasi dan Kepemimpinan Terhadap Kinerja Karyawan pada PT. Tirta Investama Langkat - Aisyah Natasha; Nashrudin Setiawan; Ahmad Aswan Waruwu (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The research aims to analyze the influence of work environment, motivation and leadership partially and simultaneously on employee performance. The population is employees who work for PT. Tirta investama Langkat totaled 173 people and the sampling technique was taken using a random sample, namely the Slovin formula so that the total sample used was 63 respondents. The type of data used in this research is primary data and the data source used is distributing questionnaires to respondents on a Likert scale. The data analysis technique uses Smart PLS. The results of this research partially show that the work environment has a positive and significant effect on employee performance, partially motivation has no effect on employee performance, partially leadership has a significant effect on employee performance. The results of this research simultaneously or as a whole show that the work environment, motivation and leadership influence employee performance. In the calculation results, the R Square value is 0.663, this means that 66.3% of variations or changes in employee performance are influenced by the work environment, work motivation and leadership, while the remaining 36.7% is explained by other reasons.